Microfluidic Technology for Cell Manipulation - Jae-Sung Kwon; Je Hoon Oh (Applied Sciences, 2018)
Microfluidic techniques for cell manipulation have been constantly developed and integrated into small chips for high-performance bioassays. However, the drawbacks of each of the techniques often hindered their further advancement and their wide use in biotechnology. To overcome this difficulty, an examination and understanding of various aspects of the developed manipulation techniques are required. In this review, we provide the details of primary microfluidic techniques that have received much attention for bioassays. First, we introduce the manipulation techniques using a sole driving source, i.e., dielectrophoresis, electrophoresis, optical tweezers, magnetophoresis, and acoustophoresis. Next, we present rapid electrokinetic patterning, a hybrid opto-electric manipulation technique developed recently. It is introduced in detail along with the underlying physical principle, operating environment, and current challenges. This paper will offer readers the opportunity to improve existing manipulation techniques, suggest new manipulation techniques, and find new applications in biotechnology.